2017
DOI: 10.1002/cbdv.201600407
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Chemical Composition, Vasorelaxant and Angiotensin I‐Converting Enzyme Inhibitory Activities of Essential Oil from Aerial Parts of Seseli pallasii Besser (Apiaceae)

Abstract: The present paper describes environmental and seasonal-related chemical composition variations, vasorelaxant and angiotensin I-converting enzyme (ACE) activities of essential oil from aerial parts of Seseli pallasii BESSER. The composition was analyzed by GC and GC/MS. Monoterpenes were found to be the most abundant chemical class with a-pinene (42.7 -48.2%) as the most prevalent component. Seseli pallasi essential oil relaxed isolated endothelium-intact mesenteric arteries rings precontracted with phenylephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…They detected IC50 value as 1.7 mg/mL [53]. Suručić et al (2017) reported that essential oil of S.pallasii showed dose-dependent inhibition capacity on ACE with an IC50 value of 0.33 mg/mL [54]. In contrast to the results from our work, Saleem et al (2017) stated that ethanol and water extracts of seeds of dill, ajowan, fennel, coriander, and anise from Apiaceae family did not show an inhibition effect on ACE [55].…”
Section: Resultsmentioning
confidence: 99%
“…They detected IC50 value as 1.7 mg/mL [53]. Suručić et al (2017) reported that essential oil of S.pallasii showed dose-dependent inhibition capacity on ACE with an IC50 value of 0.33 mg/mL [54]. In contrast to the results from our work, Saleem et al (2017) stated that ethanol and water extracts of seeds of dill, ajowan, fennel, coriander, and anise from Apiaceae family did not show an inhibition effect on ACE [55].…”
Section: Resultsmentioning
confidence: 99%
“…Essential oils from Seseli L. species have been previously examined, and germacrene D (29.8%), sabinene (10.3%), (Z)-β-ocimene (9.8%) and limonene (8.6%)] on S. annuum L. [39]; sabinene (17.7-25.1%) on S. buchtormense (Fischer) W. D. J. Koch [40]; α-pinene (26.2% and 35.8%), (E)-sesquilavandulol (11.8% and 3.2%) on S. campestre Besser fruits [41]; α-pinene (38.6±0.5%), β-pinene (17.5±0.1%) and (E)-sesquilavandulol (10.3±0.8%) on S. campestre Besser aerial parts [42]; myrcene (29.2%), α-pinene (18.6%, 21.2%), β-pinene (13.2%, 14.2%) and limonene (10.6%)] on S. tortuosum L. [43][44]; α-pinene (42.7-48.2%) on S. pallasii Besser [45]; αpinene (23.3-37.8%), sabinene (12.9-14.2%), β-phellandrene (5.1-17.4%) on S. rigidum Waldst. & Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Molecules obtained from various plant isolates have gained great interest as ACE inhibitors recently. The most promising compounds based on their structure difference could be divided in tannins, avonoids, essential oil [5,44]. Although structurally different, all these compounds have in common presence of functional groups which serve as hydrogen (H) bond acceptors or donors, such as phenolic and carboxylic.…”
Section: Ace Inhibitory Activitymentioning
confidence: 99%
“…Examination of substances of plant origin with ACE inhibitory activity shows that avonoids and peptides are the most active ACE inhibitors [4]. Regarding essential oils, few studies have studied the effects of these secondary metabolites on ACE inhibition [5][6][7][8]. Also, tannins are found to be non-speci c inhibitors of ACE, through sequestration of the enzyme metal cofactor (Zn 2+ ), precipitation of protein or as non-speci c enzyme (trypsin and chymotrypsin) inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%